Quasidifferential equations in semilinear metric spaces - Plotnikov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For quasidifferential equations in semilinear metric spaces, we consider the problem of existence, uniqueness, and continuity of solutions and the problem of justification of the averaging method.